Cardiac Manifestation of Acute Lymphoblastic Leukemia. (July 2016) - Werner, Rudolf A.; Rudelius, Martina; Thurner, Annette; Higuchi, Takahiro; Lapa, Constantin
Abstract : Abstract: Here, we report on a 38-year-old man with unclear right heart failure. Imaging with cardiac MRI and combined PET/CT with 18 F-FDG revealed a hypermetabolic mass extending from the right ventricle to the atrium. In addition, intense glucose utilization throughout the bone marrow was noted. Biopsies of both bone marrow and cardiac mass were performed and revealed precursor B-cell acute lymphoblastic leukemia with gross leukemic infiltration of the myopericardium, a rare manifestation of acute lymphoblastic leukemia at initial diagnosis.